Remote-control of multi appliances based latching circuit and DTMF - Jabbar Shatti Jahlool (Institute of Advanced Engineering and Science, 2022)
There are multiple technologies used to remotely control electric appliances like Wi-Fi, Bluetooth, global system for mobile (GSM), and dual-tone multi-frequency (DTMF), but these technologies contain limitations, whether by coverage distance or by the number of devices that are controlled remotely. In this paper, these restrictions were overcome with the use of DTMF and digital latching devices, which doubles the number of remote-controlled electrical appliances compared to other research using the same intended technology DTMF. Using the proposed mechanism in this paper enables the users to effectively control several electric remote devices equal to the standard number of mobile keypad buttons, so in this way, can control 12 devices. This is via the mobile phone by sending commands in the form of analog tones through calling to auto-answer remote control panel phone (RCPP). An interesting feature of this research, each keypad key of the owner mobile (OM) using to control one remote electric device to switch it ON or OFF, so that the first pressing will cause to switch it ON and the second pressing caused to switching it OFF. This method is used instead of using two keypad keys, one for ON and the other for OFF. The proposed idea working is the same as manually switching but here remotely and electronically. This feature is achieved by using a D-latch digital circuit. The work is implemented and tested by using Proteus simulation program.